2012
DOI: 10.1016/j.jvs.2012.04.021
|View full text |Cite
|
Sign up to set email alerts
|

The retroperitoneal approach to the abdominal aorta in the endovascular era

Abstract: The aim of this review was to assess the place of retroperitoneal (RP) aortic surgery for abdominal aortic aneurysms (AAAs) in the endovascular era and evaluate the evidence supporting it in preference to the more traditional transperitoneal approach. As endovascular graft technology improves, open aortic surgery is declining. AAAs unsuitable for endovascular aneurysm repair are, by definition, anatomically challenging. The RP approach is especially suited to anatomic challenges such as those posed by contempo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…9 In an attempt to avoid complications associated with entrance into the peritoneal cavity, the retroperitoneal approach was adopted and also offers improved access to the suprarenal and supraceliac aorta. 5, 10 …”
Section: Introductionmentioning
confidence: 99%
“…9 In an attempt to avoid complications associated with entrance into the peritoneal cavity, the retroperitoneal approach was adopted and also offers improved access to the suprarenal and supraceliac aorta. 5, 10 …”
Section: Introductionmentioning
confidence: 99%
“…In one of these studies, only the AAA was repaired, with the large osteophyte not requiring treatment, and in the other the vertebral bodies were stabilized with pedicle screws, while the AAA was left due to healthy renal arteries and distal flow from collaterals. While the left retroperitoneal approach is often preferred for AAA repair due to its ability to expose the entire infradiaphragmatic aorta with access to the suprarenal aorta, 28 the anterior approach was required for the spinal surgery in these instances. This approach was utilized to ensure the task was safely performed and extensile as required.…”
Section: Discussionmentioning
confidence: 99%
“…This approach was utilized to ensure the task was safely performed and extensile as required. It is commonly used for larger AAA repairs 28 and may allow a larger working space and natural orientation to anatomical landmarks. 29 For this particular combination of surgical procedures (vascular and spinal), a multidisciplinary approach is considered crucial in planning for success in surgical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, this reduction is a result of several factors, such as patient selection, medical treatment, aesthetic techniques, and improved care in intensive care units, and not the surgical technique per se.Traditionally, the RP approach has been reserved for selective cases as many surgeons feel it is technically more demanding and provides limited access to the aortic side branches. 3 However, several comparative studies demonstrated some advantages over the RP approach. 4,5 In clinical practice the RP approach was used for supra-renal and thoraco-abdominal aneurysms, and usually not for infra-renal aneurysms.In the last 20 years endovascular repair (EVAR) has had a major effect on clinical practice.…”
mentioning
confidence: 99%
“…Traditionally, the RP approach has been reserved for selective cases as many surgeons feel it is technically more demanding and provides limited access to the aortic side branches. 3 However, several comparative studies demonstrated some advantages over the RP approach. 4,5 In clinical practice the RP approach was used for supra-renal and thoraco-abdominal aneurysms, and usually not for infra-renal aneurysms.…”
mentioning
confidence: 99%